MELARAS PIANO DENGAN SISTEM EQUAL-TEMPERED - Musmal, Musmal (Institut Seni Indonesia Yogyakarta, 2013)
This article theoretically discusses some basic techniques for tuning the piano through the equal-tempered system. Based on long experience as a piano tuner, the author believe that this methodological steps of tuning technique can be mastered by anyone through intensive tuning excercises.Keywords: Piano, equal tempered, tuning technique.